Pemberdayaan Masyarakat Melalui Pemanfaatan Limbah Rumah Tangga Menjadi Pupuk Organik Pada Lembang Batualu Selatan - Apriyogi Apriyogi; Yunarti Daia; Seprianus Densa; Chrismesi Pagiu; Dian Intan Tangkeallo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
This service focuses on "Community Empowerment through the Utilization of Household Waste into Organic Fertilizer in South Lembang Batualu", people who do not understand how to make organic fertilizer by using used materials, people still lack understanding in terms of adapting the plants to be planted in the soil with different conditions. Therefore, this service focuses on the theme "organic farming" which aims to increase public awareness and broaden people's knowledge about organic farming, especially in making organic fertilizer using household waste. The method we use is the approach method, this method is a method carried out directly by students to inspire the community in South Lembang Batualu. The results achieved are able to help with community problems regarding organic farming in South Lembang Batualu, so that this service activity can have a positive impact, namely that the community understands more about organic farming, especially in making organic fertilizer using household waste.